2009
DOI: 10.1103/physreve.80.036204
|View full text |Cite
|
Sign up to set email alerts
|

Generic behavior of master-stability functions in coupled nonlinear dynamical systems

Abstract: Master-stability functions (MSFs) are fundamental to the study of synchronization in complex dynamical systems. For example, for a coupled oscillator network, a necessary condition for synchronization to occur is that the MSF at the corresponding normalized coupling parameters be negative. To understand the typical behaviors of the MSF for various chaotic oscillators is key to predicting the collective dynamics of a network of these oscillators. We address this issue by examining, systematically, MSFs for know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
228
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(236 citation statements)
references
References 33 publications
3
228
0
5
Order By: Relevance
“…The matrices DF and DH are the Jacobians of the vector field of the isolated system F(x) and coupling function H(x) respectively, evaluated on the synchronous solution s(t). For more details, please see for example [24], [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The matrices DF and DH are the Jacobians of the vector field of the isolated system F(x) and coupling function H(x) respectively, evaluated on the synchronous solution s(t). For more details, please see for example [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…As an illustrative example, we will consider a network of coupled identical Rössler oscillators (as in [25]) with individual dynamics governed by: …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pecora and Carroll have developed an elegant way, namely the master stability function (MSF) for analyzing the stability of complete synchronization for a network of identical dynamical systems [29]. The MSF allows one to study the stability of synchronization of different networks using a single function and has been used widely for a comparative study of synchronization of different networks of identical dynamical systems [30][31][32][33][34][35][36]. It is shown that the small world network enhances synchronizability of a network of coupled identical systems [31].…”
Section: Introductionmentioning
confidence: 99%